Macroeconomics - Mankiw, N. Gregory (Worth Publishers, 1992)
The book consists of four parts. Part one discusses why macroeconomics is an exciting and important subject: explains the tools that economists use to analyze the economy, discusses the types of data that economists and policymakers use to monitor the economy. Part two explains how the economy works: examines classical models of the economy, assumes that the inputs into production - capital and labor - are fixed, looks at the factors of production more closely, discusses the very long run over which the economy's stock of capital can change, examines the labor market in order to explain what determines the natural rate of unemployment, introduces the concept of money and discusses a key macroeconomic variable - the inflation rate, extends the classical model to describe the behavior of an economy as it interacts with the economies of other nations, discusses exports and imports, international borrowing and lending, and the exchange rate between different currencies. Part three explains short-run fluctuations: discusses the key differences between the long run and the short run, introduces the model of aggregate supply and aggregate demand, presents the IS-LM model, presents the Mundell-Fleming model, discusses theories of aggregate supply and their implications, presents some recent developments in the theory of short-run fluctuations. Part four presents microeconomic models that help refine our macroeconomic analysis: looks at how consumers behave and provides a more thorough explanation of the consumption function, examines the determinants of the three types of investment - business fixed investment, residential investment, and inventory investment, discusses the role of the banking system in determining the money supply, as well as the various theories of the money demand function. The book ends with a brief epilogue